Enhancement in Above-Threshold Ionization Spectrum (Journal of Atomic and Molecular Sciences, 2017)
Freeman resonance and resonance-like enhancement (RLE) in above-threshold ionization (ATI) spectrum are reviewed in this work. Two different interpretations accounting for the high-energy enhancements in the ATI spectra are described. One of them is the multiphoton ionization “channel closing” relating to the destructive ⁄ constructive interference, while the other pursue the fundamental concept of resonance and associates the enhancement with a resonant excited state. Primary calculation of the RLE using generalized quantum trajectory Monte Carlo method is also present.